The effectiveness of the implementation of new technologies in the prevention of purulent complications of repeated surgеries for complications of fractures of the proximal femur of patients - Kalashnikov, An. V.; Malik, V. D.; Kalashnikov, Al. V. (Zaporozhye Medical Journal, 2016)
Despite the latest achievements of modern traumatology, remains quite high percentage of unsatisfactory results of treatment of fractures of the proximal femur (fPf). According to the literature repeated surgery increases the risk of postoperative purulent complications in several times. The authors of the article developed the innovations introduced in practice based on the use of thrombocytopoiesis fibrin gel, which has a high antibacterial activity due to preservation of leukocytes (local antibiotic effect), together with bone shavings during the performing of the operations when performing reactioneze and TEP after performing osteosynthesis, and also at persons of senile and elderly, for prevention of postoperative purulent complications in fPf. A comprehensive clinical study of 120 patients with fPf complications (false joints, aseptic necrosis of the femoral head, axial deformation) after osteomyelitis who underwent re-operative intervention was provided. Patients were divided into two groups, first (control) group consisted of 60 patients with consequences fPf who underwent total endoprosthesis (TEP) of the hip joint (30 patients) and locked intramedullary nailing (LIN) (30 patients) by conventional methods. The second (experimental) group consisted of 60 patients with consequences fPf who underwent TEP of the hip joint (30 patients) and LIN (30 patients) with use developed by authors of innovations. Effectiveness of prevention of septic complications in both groups of observation was evaluated. The observation period was 1 year. There was statistically significant (p≤0.01) decrease in the number of early (4 times) and late (3 times) postoperative complications in patients of the experimental group in comparison with patients of control group. The new technologies use allows to increase in 8.4% the efficiency of preventive maintenance of purulent complications of surgical treatment of patients with complications after performing osteosynthesis in the treatment of fPf. The introduction of the proposed new technologies will allow to carry out effective prevention of purulent complications of repeated surgical interventions in the fPf treatment, which distinguishes the proposed method from the accepted methods of prevention of postoperative purulent complications fPf treatment.